2023
DOI: 10.1039/d2me00265e
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning assisted identification of the matched energy level of materials for high open circuit voltage in binary organic solar cells

Abstract: With the application of the new material and device optimization method, binary bulk heterojunction organic solar cells (OSCs) have the outstanding performance in recent years. However, the open-circuit voltage (Voc)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…That is, the deeper-lying HOMO (D) and LUMO (A) are conducive to improving the PCE of the device. Kuo Wang et al’s study showed that the deeper-lying HOMO (D) was conducive to reducing the energy range to increase the V oc [ 28 ], while the deeper-lying LUMO (A) generally contributed to the construction of narrow band-gap acceptors to broaden the NIR absorption, and thus increase the J sc [ 40 ]. Usually, the effects of the LUMO (D) and HOMO (A) on the PCE seem to be ignored.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, the deeper-lying HOMO (D) and LUMO (A) are conducive to improving the PCE of the device. Kuo Wang et al’s study showed that the deeper-lying HOMO (D) was conducive to reducing the energy range to increase the V oc [ 28 ], while the deeper-lying LUMO (A) generally contributed to the construction of narrow band-gap acceptors to broaden the NIR absorption, and thus increase the J sc [ 40 ]. Usually, the effects of the LUMO (D) and HOMO (A) on the PCE seem to be ignored.…”
Section: Resultsmentioning
confidence: 99%
“…ML, as a technique for studying how to use computers to simulate human learning activities, aims to help researchers mine and understand the laws behind big data across a wide range of fields, such as the intersection of physics, chemistry, electronics, and materials science [ 21 , 22 , 23 ]. Nowadays, ML has been widely applied in the performance prediction of PSCs and the screening and design of new materials [ 24 , 25 , 26 , 27 , 28 ], and some work related to feature engineering and algorithm optimization to improve the prediction accuracy has been reported [ 29 , 30 ]. For example, Haibo Ma’s group used the gradient boosting regression tree (GBRT) model to conduct high-throughput screening on about 10,000 candidate materials, identifying important structural units and proposing 126 new material structures, with a predictive efficiency of more than 8% [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, our team focused on voltage loss in non-fullerene OPVs, using machine learning to pinpoint key features for developing high-e ciency cells [44]. Additionally, we explore the energy level matching strategy of binary and ternary OPVs [45] and the effect of organic receptors on Voc [46]. Therefore, machine learning is pivotal in accelerate researching optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning (ML) allows researchers to excavate the hidden physical laws behind big data and draw reliable conclusions from the perspective of algorithms for more effectively accelerating material design and performance optimization in PSCs to save time and money [20][21][22]. Currently, ML has been widely applied in the field of PSCs [23][24][25][26][27]. Kakaraparthi Kranthiraja et al developed a series of novel π-conjugated polymer donor materials for NFAs based on the random forest (RF) model [23].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our group applied ML to predict the champion PCE of ternary PSCs and screen the optimal doping ratio of the third component [26]. Furthermore, we also elucidated the matching energy levels of binary PSCs materials to enhance the V oc through ML [27]. Exploring organic materials and understanding hidden chemical information via ML have become a new research model.…”
Section: Introductionmentioning
confidence: 99%